Effects of Kegel Exercises on Urinary Incontinence in the Elderly - Liana, Yunita; Jumiani , Winia (Institute Of Computer Science (IOCS), 2024)
The elderly experience of decline and changes physically, psychologically, socially, and spiritually most affect their health status. Urinary incontinence is a problem experienced by many elderly. Kegel exercises are a therapy for urinary incontinence problems. The purpose of the study was to determine the effect Kegel exercises of Kegel exercises on urinary incontinence. The study population was all elderly who experienced urinary incontinence in the working area of UPTD Puskesmas Tanjung Raya Muara Enim. The study was conducted from January 22 to February 10, 2024. The sample number was 38 people with the purposive sampling technique. This research design is pre-experimental with one group pre-post design. The instrument used to measure incontinence scores is the ICIQ-UI Short Form, with three measurements at week 1, week 2, and week 3. Data were analyzed using the Friedman test to see differences in urinary incontinence scores from the results of 3 measurements at week 1, week 2, and week 3. Based on analysis using the Friedman test, the p-value was 0,000 (p<0,050), which means there was a difference in urinary incontinence scores in the first week, second week, and third week after doing Kegel exercises. The lowest urinary incontinence score after the Kegel exercises was in the third week, with a mean rank value of = 1,34. Kegel exercises in the third week had more influence in reducing urinary incontinence scores.